2020
DOI: 10.1007/s00382-020-05233-2
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical and thermodynamical drivers of variability in European summer heat extremes

Abstract: We use the 100-member Max Planck Institute Grand Ensemble (MPI-GE) to disentangle the contributions from colocated dynamic atmospheric conditions and local thermodynamic effects of moisture limitation as drivers of variability in European summer heat extremes. Using a novel extreme event definition, we find that heat extremes with respect to the evolving mean climate increase by 70% under a moderate warming scenario during the twenty-first century. With a multiple regression approach, we find that the dynamica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 54 publications
1
45
0
3
Order By: Relevance
“…A majority of the population in South Asia depends on agriculture for their livelihood. South Asia is among the global hot spots that are likely to face the detrimental impacts of climate change 1 , 2 . Considerable changes in precipitation and temperature are projected in South Asia that will have implications for water resources and agriculture 3 – 6 .…”
Section: Background and Summarymentioning
confidence: 99%
“…A majority of the population in South Asia depends on agriculture for their livelihood. South Asia is among the global hot spots that are likely to face the detrimental impacts of climate change 1 , 2 . Considerable changes in precipitation and temperature are projected in South Asia that will have implications for water resources and agriculture 3 – 6 .…”
Section: Background and Summarymentioning
confidence: 99%
“…Third, horizontal advection has been identified as an important mechanism for severe heatwaves (e.g., Schumacher et al, 2019) which is influenced by both atmospheric and land surface conditions. Finally, Suarez-Gutierrez et al (2020) found it is necessary to examine both atmospheric (dynamics) and land surface (thermodynamics) conditions together to understand the sources of variability for heat extremes. Therefore, it is timely to understand the evolution of heatwaves according to each of the possible heat mechanisms and identify the contribution of both terrestrial and atmospheric processes.…”
Section: Introductionmentioning
confidence: 99%
“…Heat advection accompanying these systems can further enhance surface temperatures (e.g., Gibson et al, 2017;Miralles et al, 2014Miralles et al, , 2019Schumacher et al, 2019), with this process defined by both the large-scale synoptic conditions and the characteristics of the surface over which the atmospheric flow passes. Considerable research has also examined how land surface conditions contribute to local amplification of temperatures during heatwaves (e.g., Fischer et al, 2007;Gibson et al, 2017;Hirsch, Evans, et al, 2019;Miralles et al, 2014;Suarez-Gutierrez et al, 2020). In particular, in the weeks prior to a heatwave, the absence of precipitation to recharge water stores within the land surface results in a shift in the surface energy partitioning away from latent heating towards enhanced sensible heating (e.g., Hirsch, Evans, et al, 2019;Miralles et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…From a meteorological perspective, a heat wave event is produced when a high pressure system remains in the same place for a prolonged period of time, that make a heat wave event to last by advecting warm dry air to the affected region 22,28,29 . This situation is enhanced over dry soils or low humidity regions due to the extreme temperatures probability amplification [30][31][32][33][34][35][36][37] .…”
mentioning
confidence: 99%